(untitled) (BIRDEM Medical Journal, 2019)
Background: Diabetic ketoacidosis (DKA) is a major complication of type 1 and type 2 diabetes mellitus and is associated with increased risk of morbidity and mortality. Infections, non-compliance and co-morbid states are most important precipitating causes. Proper identification of the precipitating factor is very important in management of DKA. Clinical feature and management of DKA are well known and have been described in many text books and reviews in literature. However, there are a very few published large studies from Bangladesh. For this reason, this study had evaluated fifty children with Diabetic ketoacidosis and to identify their clinical features, precipitating factors and outcome. Methods: This observational study was done among admitted children with DKA in the deptartment of Paediatrics of Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital during study period between September 2016 to February 2017. Results: Fifty children were admitted with Diabetic ketoacidosis. Seventy percent were new diabetes cases and the remaining (30%) were known diabetic patient. Majority (62%) were female. Mean age was 9.31 years with 4.40 standard deviation. Infection was the commonest (62%) precipitating factor followed by insulin omission (10%). Major clinical features were dehydration (100%), polyuria (98%), Kussmaul’s breathing (60%) and abdominal pain (38%). Eighty four percent patients improved after treatment and 16% patient developed complications like acute kidney injury and septicaemia. There was no mortality. Conclusion: Infection was the commonest precipitating factor of DKA. Kussmaul’s breathing and dehydration were the commonest clinical features. Most of the patients improved after treatment Birdem Med J 2019; 9(2): 121-126